Sub-bottom profiler data of the northern Lau Basin at ~16° during SONNE cruise SO267 - Michael Riedel; Anna Jegen; Heidrun Kopp (PANGAEA, 2022)
The Atlas PARASOUND P70 system was used to acquire high resolution sub-bottom profiler data throughout most of the cruise. Two different waves with frequencies of ~18-20 kHz (primary high frequency, PHF) and a ~22-24 kHz wave were used to create a so-called secondary high (about 40-42 kHz, SHF) and a secondary low frequency (SLF) of about 4 kHz, which is used for the sub-bottom profiling. The opening angle of the transducer array is 4° by 5°, which corresponds to a footprint size of about 7 % of the water depth. Data was acquired along p02 of Sonne cruise SO267 which crosses the northern Fonualei Rift Spreading Centre and the southern Mangatolu Triple Junction about ~16° S.